Autologous Dendritic Cells Prolong Allograft Survival Through Tmem176b‐Dependent Antigen Cross‐Presentation. Issue 5 (14th April 2014) - Segovia, M.; Louvet, C.; Charnet, P.; Savina, A.; Tilly, G.; Gautreau, L.; Carretero‐Iglesia, L.; Beriou, G.; Cebrian, I.; Cens, T.; Hepburn, L.; Chiffoleau, E.; et al.
Abstract : The administration of autologous (recipient‐derived) tolerogenic dendritic cells (ATDCs) is under clinical evaluation. However, the molecular mechanisms by which these cells prolong graft survival in a donor‐specific manner is unknown. Here, we tested mouse ATDCs for their therapeutic potential in a skin transplantation model. ATDC injection in combination with anti‐CD3 treatment induced the accumulation of CD8 + CD11c + T cells and significantly prolonged allograft survival. TMEM176B is an intracellular protein expressed in ATDCs and initially identified in allograft tolerance. We show that Tmem176b −/− ATDCs completely failed to trigger both phenomena but recovered their effect when loaded with donor peptides before injection. These results strongly suggested that ATDCs require TMEM176B to cross‐present antigens in a tolerogenic fashion. In agreement with this, Tmem176b −/− ATDCs specifically failed to cross‐present male antigens or ovalbumin to CD8 + T cells. Finally, we observed that a Tmem176b ‐dependent cation current controls phagosomal pH, a critical parameter in cross‐presentation. Thus, ATDCs require TMEM176B to cross‐present donor antigens to induce donor‐specific CD8 + CD11c + T cells with regulatory properties and prolong graft survival. Abstract : Using a mouse skin transplant model combining anti‐CD3 treatment with autologous tolerogenic dendritic cell infusion, the authors demonstrate the importance of antigen cross‐presentation to prolong allograft survival mediated by CD8+ regulatory T cells by characterizing a novel cation channel, Tmem176b, that participates in the fine‐tuning of phagosomal pH in dendritic cells. See editorial by Morelli and Thomson on page 989.